He poroporoaki ki te rangatira nā tana irāmutu - King, Jason (Te Kaharoa, 2011)
Wharetoroa Robert (Bob) Kerr, a well-known respected elder from the Ngāti Mahuta tribe in Waikato, a man steeped in Māori history, knowledge and a repository of Māori lore passed away on the 29th of November, 2010 after enduring a long period of illness at the age of 93. Husband to the late Beatrice Kerr, father to Peter, Hoturoa, Manny, Bunny and John and grandfather to many mokopuna.  Wharetoroa was a man who was dedicated to preserving Māori language, customs and protocols.  He spent his life supporting the Kīngitanga and frequently spoke on behalf of the late Māori Queen, Dame Te Ātairangikaahu.  His passion was also rugby league especially with the Taniwharau Rugby League Club; he eventually became a speaker and elder for the New Zealand Māori Rugby League team.  Following is an account of a formal speech delivered in Māori at his funeral held on his Marae, Te Kōraha, situated south of Kāwhia harbour, west coast of the North Island.  Many from far and wide including the Māori King, tribal leaders, dignitaries and the like attended the funeral to farewell Wharetoroa.